The global, regional, and national patterns of change in the burden of bacterial pyoderma from 1990 to 2019 and the forecast for the next decade - Hao Wang; Zihao Bai; Chong Shen; Jiaxi Kou; Yanqing Zhu; Huaxia Xie; Chen Chen; Ran Mo (Scientific Reports)
Abstract Pyoderma, commonly known as impetigo, is a bacterial skin infection causing pus formation, prevalent globally, especially in resource-poor areas. It affects both children and adults, including those with conditions like diabetes. Despite its significant impact and economic burden, research on its global epidemiology is limited. This study aims to address this gap by analyzing pyoderma trends from 1990 to 2019 using GBD data. The study aims to analyze global trends in pyoderma epidemiology from 1990 to 2019 using GBD data. Specifically, it investigates Age-Standardized Incidence Rate (ASIR), Mortality Rate (ASMR), and Disability-Adjusted Life Years Rate (ASDR) across 204 countries. Additionally, it provides insights into demographic and socioeconomic factors influencing pyoderma prevalence. Furthermore, it forecasts pyoderma’s development trends for the next decade to inform public health strategies. Data were sourced from the GBD 2019 database, comprising various sources such as censuses, surveys, and registries. Estimates for pyoderma incidence, mortality, and DALYs, along with their 95% uncertainty intervals (UI), were retrieved. The Sociodemographic Index (SDI) was used to assess socioeconomic status, and statistical calculations were performed using the WHO Health Equity Assessment Toolkit and R software (v4.3.2). From 1990 to 2019, the Age-Standardized Incidence Rate (ASIR) and Age-Standardized Mortality Rate (ASMR) of impetigo increased, while the Age-Standardized Disability-Adjusted Life Years Rate (ASDR) declined. Significant global geographical heterogeneity persists, closely associated with the Sociodemographic Index (SDI). Children under 5 and the elderly are particularly at risk, with lower SDI nations bearing higher burdens. Population growth and aging contribute to this rise, with disparities in impetigo trends persisting among countries and regions with varying SDI levels, expected to continue until 2030. Pyoderma exhibits significant heterogeneity across age, gender, and geography, with pronounced disparities evident in underdeveloped regions or countries. Therefore, prioritizing policy formulation and implementing tailored prevention and treatment strategies for high-risk populations are imperative to alleviate the disease burden effectively. Such targeted approaches are crucial in addressing the global impact of pyoderma.